CONVENTIONAL BANK CONVERSION ANALYSIS TO SHARIA BANKS ACOORDING TO THE SERVICES AUTHORITY REGULATION - Nurhadi Nurhadi (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2019)
OJK (financial services authority) that issues a rule about conventional banks can make changes to business activities into Islamic banks, but not vice versa. Changes must obtain permission and fulfill the requirements. After permission is obtained, it must clearly state the word "Sharia" on the writing of the name, and the iB logo on the forms, documents, products, offices, and networks of Sharia Bank offices. The legal basis is: 1). Law Number 7 of 1992 concerning Banking as amended by Act Number 10 of 1998 concerning Amendment to Law Number 7 of 1992 concerning Banking; 2). Law Number 21 of 2008 concerning Sharia Banking; 3). Financial Services Authority Regulation Number 64 / POJK.03 / 2016 Year 2016 concerning Changes in Conventional Bank Business Activities to Sharia Banks; 4). Financial Services Authority Circular Letter Number 2 / SEOJK.03 / 2017 Year 2017 concerning Changes in Business Activities of Conventional Commercial Banks to Islamic Commercial Banks. The mechanism described above must be carried out by conventional banks that want to change business activities into Islamic banks